Immediate and Long-Term Effects of Breathing Exercises on Reaction Time - Burçin Akçay; Ozan Bahadır Türkmen; Ebru Kaya Mutlu; Canan Demir; Ahmet Kurtoğlu; Kopzhassar Bayetov; Madawi H. Alotaibi; Safaa M. Elkholi (Medicina, 2024)
Background and Objectives: The aim of this study was to investigate the immediate and long-term effects of breathing exercises on simple and choice reaction time. Materials and Methods: A total of 31 participants were included in the study. The participants were randomly divided into two groups. The intervention group (IG; n:16) received 12 sessions of breathing exercises for four weeks (three days a week), while the control group (CG; n:15) received no intervention. Both groups underwent the same assessments at the same times: at baseline, after the first exercise session, and after four weeks/after 12 exercise sessions. Reaction time was assessed using three conditions: choice reaction time (CRT) of the upper limb, auditory reaction time (ART), and visual reaction time (VRT) tests. The first assessment was applied at baseline. The second assessment measured the short-term effect of the breathing exercises after the study group received their first breathing exercise session. The third assessment, to determine the long-term effect, was repeated four weeks after the baseline (A4W) assessment after completing 12 breathing exercises. Results: There was no significant difference between the groups at baseline, immediately, and A4W (p < 0.05) for the VRT, ART, and CRT results with the dominant hand (DH), whereas a group-by-time interaction was found only for the visual reaction time results with the non-dominant hand (nDH) (p > 0.05). Conclusions: The results of this study, which included the evaluation of the immediate and long-term effects of breathing exercises on reaction time, showed an improvement in visual reaction time between the groups over time. In further studies, it is recommended to evaluate the changes and responses in the central nervous system with objective methods to reveal the effect of breathing exercises on reaction time more clearly.